Rancang Bangun Kunci Pintu Rumah Berbasis Internet of Things (IoT) - Mahendra Peratama; Ahmad Syazili (APTIKOM SUMSEL, 2022)
One of the problems of theft of goods at home is often caused by our own negligence as homeowners who forget to lock the door of the house when traveling. In addition to the problem of failing to lock the door which makes unknown people enter the house. Forgetting to put the key or worse, we could lose the key to our house, and the key could be found by someone with malicious intent and on us or our family. By utilizing the Internet of Things (IoT), a device is developed that can open and lock the door of the house, so that homeowners no longer have to worry about forgetting to lock the door. Using Nodemcu esp8266 which is already equipped with a wifi module to be able to connect to the internet, and can be controlled via an application on a smartphone via the internet